Evaluation of fungicides for the management of Taphrina leaf blotch of turmeric (Curcuma longa L.) - Singh, A K Singh, S Edison, Shashank (Journal of Spices and Aromatic Crops, 2000)
Evaluation of six fWlgicides for the management of leaf blotch disease of turmeric (Curcuma longa), caused by Taphrina maculans, at Madhya Pradesh, India, indicated that all the fungicides reduced the disease severity significantly over control. Lowest disease severity and highest fresh rhizome yield was recorded in Ridomil (500 ppm) which was on par with thiophanate methyl (0.1%), carbendazim (0.1%), Blitox (0.3%) and Antracol (0.3%). Apparent rate of infection was lowest in thiophanate methyl spray followed by Ridomil spray.